2010
DOI: 10.1080/10911350903126932
|View full text |Cite
|
Sign up to set email alerts
|

Does Attitudinal Consensus Lead to Neighborhood Collaboration? An Exploratory Analysis of an Urban Community

Abstract: This article examines whether high levels of attitudinal consensus on community needs and civic responsibilities among a community's residents are associated with effective collaborative efforts among that community's neighborhood associations. Drawing upon both quantitative and qualitative data from an evaluation of an umbrella organization in an urban community, the authors found only a weak connection between attitudinal consensus, which was strong to moderate on most issues, and effective neighborhood asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…A wide range of participants with diverse experiences and perspectives are assets in community-based problem-solving approaches because consensus among and across a broad base of stakeholders is more effective in creating sustainable changes than simply finding agreement among a community’s established leadership (Hyde & Meyer, 2010). One way to problem solve with a diverse group of community members is to form a community coalition.…”
mentioning
confidence: 99%
“…A wide range of participants with diverse experiences and perspectives are assets in community-based problem-solving approaches because consensus among and across a broad base of stakeholders is more effective in creating sustainable changes than simply finding agreement among a community’s established leadership (Hyde & Meyer, 2010). One way to problem solve with a diverse group of community members is to form a community coalition.…”
mentioning
confidence: 99%
“…Social networks scholars frequently find that shared beliefs facilitate collaboration (Ingold andFischer 2014, Diani et al 2018). In contrast, when examining neighborhood association collaborations, Hyde and Meyer (2010) found only a weak connection between attitudinal consensus and effective collaboration, concluding that shared attitudes among organizational leaders are insufficient for creating stable partnerships. Their mixed-method approach enabled the identification of the most significant factors, i.e., trust, legitimacy, and the need for continued engagement, and demographic differences such as race that affect the possibility of sustained collaboration.…”
Section: Organizational Characteristicsmentioning
confidence: 72%
“…Discussions about the role of NPOs in regional or local development have shown that the role of leadership is usually hidden behind the NPO and not explicitly displayed. Leadership in regional or local development has been studied mainly in smaller communities which were seen as more problematic, where competent leadership is more critical (Beer and Clower, 2014;Hyde and Meyer, 2010;James et al, 2015). This is due to the concentration of social problems that need to be solved or is a result of private activities.…”
Section: Npos In Regional and Local Governancementioning
confidence: 99%